2015
DOI: 10.1136/gutjnl-2014-308781
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen Cell Adhesion Molecule 1 long isoform modulates malignancy of poorly differentiated colon cancer cells

Abstract: Objective Nearly 20%–29% of patients with colorectal cancer (CRC) succumb to liver or lung metastasis and there is a dire need for novel targets to improve the survival of patients with metastasis. The long isoform of the Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1-L or CC1-L) is a key regulator of immune surveillance in primary CRC, but its role in metastasis remains largely unexplored. We have examined how CC1-L expression impacts on colon cancer liver metastasis. Design Murine MC38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Additional reported data suggested that CCL2 induced EMT through the activation of STAT3 signals [ 33 , 40 ] and inhibited STAT3 signaling to reduce the invasiveness of tumor cells [ 41 , 46 ]. Our data showed that Tan-IIA could inhibit the p-STAT3 (Tyr705) in a time- and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reported data suggested that CCL2 induced EMT through the activation of STAT3 signals [ 33 , 40 ] and inhibited STAT3 signaling to reduce the invasiveness of tumor cells [ 41 , 46 ]. Our data showed that Tan-IIA could inhibit the p-STAT3 (Tyr705) in a time- and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that CEACAM1 actively contributed to tumor progression [25]. The reason for this discrepancy warrants further investigation but could be that CEACAM1 may have different roles in different cancers as discussed above [26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1, also termed CD66a) is a transmembrane protein that has been recognized as an important tumor-associated factor which suppresses or promotes carcinogenesis in a context-dependent manner 13 14 , but it remains unknown whether CEACAM1 has any role like p53 in cardiovascular disease. Although it was originally identified as a tumor-associated gene 15 16 17 , CEACAM1 has been found to promote apoptosis of various cells such as pulmonary and mammary epithelial cells 18 19 , oral keratinocytes 20 , cancer cells and Jurkat T cells 21 22 .…”
mentioning
confidence: 99%